Reflexões sobre o estágio supervisionado no ensino fundamental EJA na escola José Henrique / Castanhal - PA - MOURA, Lucielma Rocha de (2023)
The supervised internship, in addition to being a requirement for undergraduate courses, is also a time for the intern to approach their future work environment. Therefore, this work aims to report and reflect on the experiences lived during the Supervised Internship of the Mathematics course in the class of the 3rd Stage of Elementary Education in the modality of Youth and Adult Education at the José Henrique de Araújo school, which is located in Agrovila Castelo Branco, rural environment in the municipality of Castanhal-PA. We address important issues such as the pedagogical practice of the mathematics teacher in the 3rd stage of Elementary School and in the Youth and Adult Education (EJA) class and the difficulties for carrying out a good internship, as well as what it provides us as future teachers. All of this based on readings by authors who work in this perspective such as Carvalho (2019), among several authors. But, also from our internship experience, showing what was possible to observe during the internship period, which took place from August to December 2012. We will address some important aspects of the internship, such as, for example, the difficulties encountered during this process, observation and conducting classes and contact with the school, showing how important the internship is in the formation of a good geography teacher.